Perbedaan Intensitas Nyeri Haid Sebelum dan Sesudah Diberikan Kompres Hangat pada Remaja Putri di Universitas Dharmas Indonesia - Husna Husna (Journal for Quality in Women's Health, 2018)
Adolesence or adolescence comes from the Latin adolescere (the difference is adolecentia, which means teenager) which means "body" or grow into adulthood. In englishmurabaqoh is adolecence which means at-tadaruj (gradual). So the meaning is gradually towards physical, resourceful, psychological, and social and emotional maturity. Dysmenorrhoea is pain during menstruation, usually with cramping and is concentrated in the lower abdomen. Complaints of menstrual pain can occur ranging from mild to severe. The severity of dysminorrhoea is directly related to the length and amount of menstrual bleeding. As is known menstruation almost always followed by a feeling of heartburn / pain.